Immune Checkpoint Inhibitor Induced Hepatitis Injury: : Risk Factors, Outcomes, and Impact on Survival - Hamouda, Danae (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.